Albeni Falls Correspondence, - Fuller, George W. (George Washington), 1876-1940
Four letters between George W. Fuller and W. C. Barnes of the United States Geographic Board in 1928 concerning the spelling and origin of the name Albeni Falls in Kootenai County, Idaho.